Black Holes, Lasers and Data Analysis: Contributions to Gravitational Wave Searches with the ExcessPower Pipeline - Chamberlin, Sydney J. (Proceedings of the Wisconsin Space Conference, 2015)
Gravitational waves (GWs) are tiny perturbations to the spacetime structure of the universe that propagate freely as wavelike solutions to the Einstein equations. The direct detection of GWs is currently a major goal in experimental physics, and a number of large scale efforts to detect them are currently underway.